Proposed guidelines to implement flexible-plastic circular economy business models in Colombia - Nicolás Ramiro Orrego-Bustamante; Amalia Alejandra Báez-Niño; Darling Perea-Cabarcas; Henry Adolfo Lambis-Miranda (Ciencias Ambientales)
[Introduction]: The lack of feasible circular economy models for recycling single-use plastics poses a significant challenge to sustainable waste management. Single-use plastics, particularly flexible types, contribute to environmental pollution and require effective recycling strategies. [Objective]: This study aimed to analyze global recycling models for single-use plastics under key parameters: type of pollutant, impacts on sustainability, value generation, stakeholders involved, and level of technology. [Methodology]: A global review of 21 circular economy models focused on single-use flexible plastics was conducted, evaluating their feasibility and effectiveness. Six models were identified as the most relevant based on the selected criteria. [Results]: The findings indicate that improving eco-efficiency requires the integration of physical and chemical recycling processes to achieve cost reductions. Additionally, maintaining a constant flow of recyclable materials is essential, emphasizing the critical role of material collection and classification cooperatives. In Colombia, the collection and classification of plastic materials emerged as a pivotal element for the long-term sustainability of recycling models. [Conclusions]: The study highlights the necessity of combining technological and logistical efforts to enhance recycling processes. Strengthening material recovery systems and cooperative efforts is crucial for advancing circular economy goals in the context of single-use plastics.